OC-041 IL28B haplotypes and IP-10 predict treatment response for recurrent HCV post transplant. (28th May 2012) - Joshi, D; Carey, I; Bruce, M; Barnabas, A; Knighton, S; Heneghan, M; Aluvihare, V; Suddle, A; Heaton, N; O'Grady, J; Agarwal, K
Abstract : Introduction: Hepatitis C virus (HCV) recurrence post liver transplant (LT) is universal. Sustained virological response (SVR) rates post LT with pegylated interferon (PEG-IFN) and ribavirin (RIB) range between 26% and 50% and are associated with significant side effects. Single nucleotide polymorphisms (SNPs) rs12979860 near the IL28B gene predict response to treatment. Strong immune T helper type 1 responses towards HCV determine also play an integral role in the outcome of infection. Interferon γ inducible protein 10 (IP-10) has been shown to correlate with treatment response in HCV mono-infection and HIV co-infected patients but limited data are available for patients in the post LT period. Our aim was to investigate whether SNPs near IL28B gene rs12979860 and pre-treatment plasma levels of IP-10 can predict treatment response in patients with recurrent HCV post LT. Methods: Pre-treatment plasma samples were studied in HCV patients post LT. Plasma levels of IP-10 (pg/ml) was measured by ELISA. rs12979860 were tested by direct sequencing. All patients were treated with PEG-IFN α 2a and weight based RIB for a minimum of 48 weeks irrespective of genotype. Virological response was divided into SVR, null-response (NR) and responder relapse (RR). All results are presented as medians (range). Results: 41 patients (34 male) with recurrent HCV (49% genotype one disease) were treated at a median time of 43 months (3–133) post LT. 71% of patients were maintained on tacrolimus monotherapy. Nine patients had been treated previously with PEG-IFN and RIB. Median baseline HCV viral load was 2.35E6 IU/ml. 78% of patients were commenced on a low accelerated dosage regimen (median dose PEG 135 μg, median dose RIB 800 mg). Rs12979860 haplotype CC was present in 24% (8×SVR, 2×RR), CT 59% (10×SVR, 9×NR, 5×RR) and TT in 17% (1×SVR, 6×NR). SVR was achieved by 19 patients (46%), 15 patients were NR (37%) and 7 were RR (17%). Baseline IP-10 levels correlated with serum AST (r=0.48, p=0.003), ALT (r=0.36, p=0.05), fibrosis score (r=0.33, p=0.04) and necro-inflammatory score (r=0.54, p=0.001). IP-10 levels were lower in those who achieved a SVR (116 vs 490, p<0.0001). IP-10 levels were higher in the NR group compared to the SVR and RR groups (545 vs 116 vs 320, p<0.0001). AUROC analysis identified IP-10 to be a significant predictor of SVR (0.84, 0.71–0.97, p<0.0001). CC haplotype and IP-10 <154 pg/ml had a 100% PPV for SVR. Conclusion: Our data demonstrates that patients with a lower baseline IP-10 level are more likely to achieve a SVR. The IL28B CC haplotype in conjunction with a low IP-10 level predicts treatment success in recurrent HCV post LT. Competing interests: None declared.